Effect of biochar amendment on soil‐silicon availability and rice uptake. Issue 1 (8th October 2013) - Liu, Xiaoyu; Li, Lianqing; Bian, Rongjun; Chen, De; Qu, Jingjing; Wanjiru Kibue, Grace; Pan, Genxing; Zhang, Xuhui; Zheng, Jinwei; Zheng, Jufeng
Abstract Rice growth and its resistance to pests had been often constrained by soil‐silicon (Si) availability. The purpose of this study was to assess the potential of biochar soil amendment (BSA) to improve Si availability in paddy soils. A cross‐site field trail with BSA was conducted in six locations with different climatic and crop‐production conditions across S China. Plant‐available Si content before field‐trials establishment and after rice harvest, as well as Si content in rice shoot were determined. Varying with site conditions, plant‐available Si content of soil was observed to increase significantly with BSA in most sites. Significant increase in rice shoot Si was detected in four out of the six sites, which was well correlated to the concurrent increase in soil pH under BSA treatment. This study demonstrates an important role of BSA to improve Si availability and uptake by rice mainly through increasing soil pH of the acid and slightly acid rice soils.